Gazelletta kashiwaensis sp. nov. (Medusettidae, Phaeodaria, Cercozoa), Its Morphology, Phylogeny, Distribution, and Feeding Behavior. (30th March 2018) - Nakamura, Yasuhide; Somiya, Rei; Kanda, Masaru; Yamaguchi, Atsushi; Tuji, Akihiro; Hori, Rie S.
Abstract: A phaeodarian morphotype, characterized by the feet surrounded with forked pedal spines with anchor‐like structures, was collected in the subtropical North Pacific. Considering the morphological and phylogenetic uniqueness, this morphotype is described as Gazelletta kashiwaensis sp. nov. The distribution of this new species is possibly affected by the Kuroshio Current. The feeding behavior of living phaeodarians was first filmed: the present new species floated in the water column stretching "protoplasmic webs" and collected diatoms by repeating the expansion and retraction of "pseudopodium‐like tentacles".